AB0961 Differentiation of rabbit adipose tissue-derived stem cells into a chondrocyte-like phenotype "in vitro" facilitated by collagen type v. (23rd January 2014) - Goldenstein-Schainberg, C.; Cruz, I.B.; Fuller, R.; Velosa, A.P.; Carrasco, S.; Capelozzi, V.; Yoshinari, N.H.; Teodoro, W.R.
Abstract : Background: Osteoarthritis (OA) is a joint pain syndrome that leads to dysfunction consequent to joint degeneration. Current available therapiesforOAare mostly symptomatic with little influence onregenerativeaspects. Thoughanti-inflammatory drugshave aneffectonpain reductionandcontrol of inflammatory processes they may not be sufficientin more advanced stagesofcartilage degeneration. Among a variety of biological functions, including an anti-inflammatory effect, collagen V (COLV) regulates the diameter of collagen fibers with a relevant role in the development of functional tissues. Objectives: To evaluate, in rabbits, the influence of COLV in the induction of differentiation of adipose tissue-derived stem cells to a chondrocyte-like cell phenotype. Methods: Rabbits New Zealand were used as source of adipose-tissues for the isolation of mesenchymal stem cells (MSCs). Preliminary characterization of mesenchymal lineage and differentiation into chondrocyte-like phenotype was confirmed by immunofluorescence analysis using antibodies to collagens I, II (polyclonals), III and CD34 (monoclonals). After 2 and 3 weeks in culture, in the presence or absence of COLV, cell aggregates were fixed for 2 hours in 4% formaldehyde, then dehydrated with etanol and washed with xylene. After embedded in paraffin, different sections were stained with Toluidine blue, Alcian blue and Picrosirius for evaluation in the optic microscope. Results: Proteoglicans and collagen were demonstrated by Picrosirius staining confirming the existence of collagen expression. Remarkably, compared to control cultures, in the presence of COLV stimulation, MSCs were capable to increase collagen I and II expressions confirming its chondrocyte-like cell phenotype. Conclusions: COLV may facilitatethe differentiation of rabbitadipose tissue-derived stem cells into a chondrocyte-like phenotype. Further studies are urged in order to evaluate the influence of this protein in the ability of chondrocytes to remodel osteoarthritic joint surface at ultra structural and molecular levels. As a result, the role of COLV in osteoarthritis physiopathology, its clinical significance and therapeutic implications could be elucidated. Disclosure of Interest: C. Goldenstein-Schainberg: None Declared, I. Cruz: None Declared, R. Fuller: None Declared, A. Velosa: None Declared, S. Carrasco: None Declared, V. Capelozzi: None Declared, N. Yoshinari: None Declared, W. Teodoro Grant/Research support from: FAPESP – 2010/17824-8, Federic Foundation Grants, FFMUSP.